Multimode MALDI-MSI deciphers matrine-induced metabolic reprogramming in prostate cancer xenografts: spatial mapping of low-molecular-weight compound alterations - Xu, Jia; Qin, Liang; Liang, Xiao; Chen, Lulu; Wang, Juexin; Guo, Hua; Wang, Fengmei; Wu, Ran; An, Xiaojing; Liu, Wenjuan; Wang, Xiaodong; Li, Qi (Frontiers in Pharmacology, 2025)
BackgroundMatrine, a bioactive isoquinoline alkaloid, exhibits antitumor efficacy by modulating multiple signaling pathways to suppress cancer cell proliferation, migration and invasion. However, its metabolic regulatory mechanisms in prostate cancer intervention require systematic characterization.MethodsWe implemented matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) for spatial metabolomic profiling of prostate tissues, integrated with multivariate analytical approaches including principal component analysis, Pearson correlation-based clustering heatmap, partial least squares-discriminant analysis, and hierarchical clustering heatmap analysis. This multimodal strategy enabled comparative evaluation of low-molecular-weight metabolite distributions across normal control, prostate cancer, and matrine-treated prostate cancer cohorts.ResultsMulti-omics integration identified 19 discriminant metabolites (VIP >1.0) spanning lipid signaling mediators (choline, glycerophosphoglycerol, sphinganine, glycerophosphoinositol, linoleic acid, oleic acid, N,N-Dimethylsphingosine), amino acid network regulators (cysteic acid, 5-Hydroxylysine, glutamine-glutamate axis components), nucleotide biosynthesis (adenine, Ribose 1,5-bisphosphate, uracil, dihydrouracil, deoxyinosine, adenosine), markers of oxidative damage (8-Hydroxyguanine) and cofactor of nitric oxide synthases and aromatic amino acid hydroxylases (tetrahydropteridine). Linoleic acid, oleic acid, and N,N-Dimethylsphingosine exhibited the highest levels in the NC group; these metabolites were significantly downregulated in the PCa group and partially restored in the PCa+MAT group. In addition, the results revealed a progressive depletion of tetrahydropteridine across experimental groups, with the PCa+MAT group exhibiting significantly lower tetrahydropteridine levels compared to both NC and PCa groups (PCa+MAT < NC < PCa). Notably, the expression levels of other compounds were the lowest in the NC group, while they were significantly upregulated in the PCa group and with intermediate levels observed in the PCa+MAT group. Spatial metabolomics delineated dynamic metabolic reprogramming during prostate cancer progression, with matrine treatment demonstrating partial reversal of cancer-associated metabolic shifts, particularly in lipid pathways, underscoring its potential as a modulator of oncogenic metabolism.ConclusionThis study establishes MALDI-MSI as a powerful platform for pharmacometabolomic evaluation, while elucidating matrine’s therapeutic potential through coordinated regulation of lipid metabolic remodeling, amino acid/nucleotide biosynthesis pathways and oxidative stress responses. Our findings provide mechanistic insights into matrine’s anticancer action and validate metabolomic approaches for natural product evaluation.